Impact of climate change on snow covered area over the transboundary Jhelum River basin of Himalayas region using Remote Sensing - Munawar, Saira; Rahman, Ghani; Miandad, Muhammad; Khan, Mehtab Ahmed; Ashraf, Humayun; Yousaf Zai, Saba (Ecological Questions, 2022)
Climate change is one of the pertinent issues for the 21st century mainly for the transboundary river basins because it has parallel impacts on the hydrosphere and cryosphere. The temperature changes impacted the snow-covered area (SCA) of the river basins. MODIS MOD10A2 product data was used to delineate the SCA for the Jhelum River basin. The catchment is further divided into elevation zones using DEM to delineate the SCA for every zone. The temperature changes were plotted against the SCA, and correlation analysis was used to see the impact of climate change on the SCA. The seasonal trend of SCA has depicted an increase in SCA during the spring and summer seasons and decreasing trend during autumn while winter shows stability. The snow cover depletion curve (SCDC) showed that snow is maximum in December, January, and February while its minimum during July and August. The correlation analysis of temperature and SCA for the period of 2001-2017 illustrated the inverse relationship, which depicted that a slight increase in temperature may trigger the fastest depletion in the snow-covered areas generating water issues for snow/glacier-fed river basins.